2015
DOI: 10.1128/jvi.00757-15
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Beta and Interferon Alpha 2a Differentially Protect Head and Neck Cancer Cells from Vesicular Stomatitis Virus-Induced Oncolysis

Abstract: Oncolytic viruses (OV IMPORTANCEThere has been a great deal of progress in the development of oncolytic viruses. However, a major problem is that individual cancers vary in their sensitivity to oncolytic viruses. In many cases this is due to differences in their production and response to interferons (IFNs). The experiments described here compared the responses of head and neck squamous cell carcinoma cell lines to two IFN subtypes, IFN-␣2a and IFN-␤, in protection from oncolytic vesicular stomatitis virus. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Similar to other RNA viruses such as measles virus (14), Sendai virus (SeV) (15), mumps virus (16), vesicular stomatitis virus (17,18), parainfluenza virus type 3 (PIV3) (19), and respiratory syncytial virus (RSV) (20), NDV can establish persistent infection under some circumstances, as reported previously (15,21,22). For establishment of persistent infection in vitro, there is normally a fine dynamic equilibrium between virus infection and viral clearance by host innate immune responses.…”
mentioning
confidence: 76%
“…Similar to other RNA viruses such as measles virus (14), Sendai virus (SeV) (15), mumps virus (16), vesicular stomatitis virus (17,18), parainfluenza virus type 3 (PIV3) (19), and respiratory syncytial virus (RSV) (20), NDV can establish persistent infection under some circumstances, as reported previously (15,21,22). For establishment of persistent infection in vitro, there is normally a fine dynamic equilibrium between virus infection and viral clearance by host innate immune responses.…”
mentioning
confidence: 76%
“…Although Stojdl et al . showed that around 80% of the tested tumor cell lines had lost the capacity to mount an antiviral response upon IFN‐I exposure, several tumor cell lines are still responsive to IFN‐I . Also in PCa, Dunn et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although Stojdl et al showed that around 80% of the tested tumor cell lines had lost the capacity to mount an antiviral response upon IFN-I exposure, 12,14 several tumor cell lines are still responsive to IFN-I. 17,29,30 Also in PCa, Dunn et al showed loss of IFN-I response in some cell lines, 31 while other studies have shown that IFN-I induced genes are active and play an important role in protecting cells from VSV infection. 32 Using a larger panel of PCa cell lines, we have now observed considerable heterogeneity in the IFN-I induced antiviral response.…”
Section: To Be Inhibited By Type I Interferon In Interferon-competentmentioning
confidence: 98%
“…This difference could be due to the threshold for induction of type I IFN signalling being raised in some cancer cells compared to normal cells (e.g. receptor levels, negative regulatory factors) and to IFNb binding with 1000-fold higher affinity to IFNAR than IFN-a2a [32]. Previously, cellular IFN-l (type III IFN) produced during VSV infection was shown to enhance VSV therapy in the B16ova/C57Bl/6 mouse model by activating NK cells against B16ova cells [33].…”
mentioning
confidence: 99%